Declaring urban conservation areas: the Art Deco townscape of Vredehoek, Cape Town - Jongens, Nicoline (School of Architecture, Planning and Geomatics, 2018)
The research question posed in this study asks what qualities, characteristics and cultural significance need to be embodied within an urban environment that make the area worthy of conservation-oriented protection through laws and policies. The research question was explored through an assessment of the townscape of Vredehoek, an informally(1) proposed conservation area in Cape Town where there is a relatively high concentration of Art Deco buildings. The selection of Vredehoek as a laboratory within which to ask this question is due to the presence of contested opinions amongst various stakeholders and heritage-claimants about the cultural significance embodied within the built fabric of this place. This study aimed to identify what elements of the built environment of Vredehoek are of special interest, what qualities and characteristics these elements of special interest embody, to understand and articulate the values that inform these qualities, and to identify to whom these elements are valuable and why. Criteria were established with which to determine whether the identified qualities and values are special enough that when synthesised, the resultant significance of the place warrants protection through heritage area designation. The criteria developed with which to assess and evaluate proposed urban conservation areas, including Vredehoek, require that such environments need to embody cultural significance and characteristics informed by an urban history reflected in its authentic manifestations developed over time through continuity of use with a high townscape quality established primarily through the aesthetic unity of its component parts. Through historical research, the studying, mapping and analysis of the area's urban morphology, built environment and natural landscape, and the identification and evaluation of values held by heritage-claimants and views held by those critical of Vredehoek's proposed designation, evidence regarding the conservation-worthiness of Vredehoek has been assembled and assessed within the framework of criteria developed to evaluate heritage area designation. It has been found that the environment of Vredehoek does not embody high townscape quality nor does a strong aesthetic unity of its components exist. Furthermore, the area is not a richly layered environment reflecting continuity of use, the existence of cultural significance within the place is limited to a relatively small part of the townscape - a collection of Art Deco buildings demonstrating a moderate degree of architectural merit. Thus the environment of Vredehoek does not meet the criteria required for heritage area conservation.